Utilizing process mining with large synthetic datasets : A case study on chemotherapy treatment for breast cancer - Fatin Izzati, Ramli (Hellenic Operational Research Society (HELORS), 2023)
This paper presents a case study on integrating process mining using a large synthetic dataset of breast cancer cases named Simulacrum. The aim was to analyze the chemotherapy treatment process through process mining. However, challenges were encountered due to the absence of experts for guidance. This study discusses the challenges faced, potential opportunities, and the essential requirements for successfully integrating process mining with significant datasets.